PENGGUNAAN METODE SUPPLY CHAIN OPERATION REFERENCE (SCOR) UNTUK MENGUKUR KINERJA DI PERUSAHAAN XYZ - I Gusti Gede Bagus Anom Juliana Putra, Anak Agung Istri Agung Sri Komaladewi, Desak Ayu Sista Dewi, (JURNAL RISET DAN APLIKASI TEKNIK INDUSTRI, 2023)
XYZ company is one of the companies engaged in the chicken farming industry. From the results of observations that have been made, the company has never carried out performance measurements so it is necessary to measure the performance of Supply Chain Management. This measurement will later be used as a basis for improvement to improve Supply Chain Management performance by identifying which indicators are used to measure performance. Supply Chain Management performance measurement is carried out using the Supply Chain Operation Reference (SCOR) method. The results of this study contained 5 attributes and 54 indicators obtained from the company which then calculated the actual value then carried out the weighting by giving a level of importance questionnaire then normalizing the snorm de boer to equate the metric values used as measurement indicators. Performance attribute values obtained reliability 64.163 (average), responsiveness 80.833(good), agility 58.163(average), cost 73.021(good), and social 100(excellent). Proposed improvements are made to the attributes that have low performance, namely the attributes of reliability and agility